Dendritic Solidification and Physical Properties of Co-4.54%Sn Alloy with Broad Mushy Zone - Weili Wang; Wenhui Li; Ao Wang (Metals, 2023)
The high undercooling of binary Co-4.54%Sn alloy has a significant influence on its microstructural characteristics and physical properties. Here, we report that the dendritic growth and physical properties of broad-temperature-range Co-4.54%Sn alloy remarkably depends on the undercooling during the rapid solidification. The maximum undercooling attains 208 K at molten state, and the dendritic growth velocity is quite sluggish in highly undercooled liquid Co-4.54%Sn alloy because it has a broad solidification range of 375 K (0.21 <semantics>TL</semantics>); the maximum value is only 0.95 m/s at the undercooling of 175 K, which then decreases with undercooling. The microstructure refines visibly and the volume fraction of the interdendritic βCo3Sn2 phase obviously decreases with undercooling. The microhardness and electrical resistivity increase with undercooling owing to the enhancement of solute content of the primary αCo phase and refinement of the microstructure where the increased crystal boundary hinders the electronic transmission. Meanwhile, the saturation magnetization also reduces with undercooling due to the crystal particle and boundary increasing significantly, and the dendritic growth velocity and solute content increase in the primary αCo phase under rapid solidification.